The adaptable law enforcement officer: Exploring adaptability in a covert police context - Oleszkiewicz, Simon (Legal and criminological psychology, 2022)
Adaptability refers to cognitive, behavioural and emotional adjustments that assist in effectively responding to novel and uncertain situations. It is acknowledged as a key attribute of the successful management of dynamic interpersonal interactions. Yet, adaptability remains largely unstudied in the field of psychology and law. Here, we take the first steps to fill this research gap. In Study 1, university students (n = 30) acted as ‘agents’ that had to complete three ‘undercover missions’ that required an adaptive response. Adaptability was measured through a self-report scale. In Study 2, practitioners (n = 22), experienced with covert policing, watched recordings of the undercover missions from Experiment 1. The practitioners rated the adaptive responses of the agents, as well as their ability to attain the mission objectives. The findings showed that our experimental set-up successfully elicited adaptive behaviour. Practitioners’ ratings of adaptability were strongly related to their ratings of trustworthiness, rapport and belief in whether the agent would accomplish their missions, but not with actual mission success. The results highlight the potential importance of adaptability for law enforcement contexts.